Determinants Influencing Commission Agents’ Intention towards Agricultural Grain Markets in India - Hansdeep Kaur Dr. Vikram (International Journal of Advanced Science and Technology, 2020)
The present study examines the determinants which influence commission agents’ intention towards agricultural grain markets. The study is based on primary data, collected from a total number of 244 commission agents belonging to different areas of Punjab state. These respondents were interviewed through a well-structured, pretested research schedule. From the literature review, various factors such as commission agents’ intention, market committee, and infrastructure, lack of assistance, cost aspect, transportation facilities, and lack of IT support have been identified in the current study. Based on those factors, a conceptual model was developed in which the factors are taken as independent factors or exogenous variables and their effect was checked on the dependent variable of ‘commission agent’s intention’. Structural equation modeling (SEM) technique has been used in the current study to examine the relationships between the exogenous and endogenous constructs. Result of research represented that all the variables have significant impact on commission agents’ intention towards agricultural grain markets.